Who is the author: genuine, honorary, ghost, gold, and fake authors? - Eugenio Picano (Exploration of Cardiology, 2024)
While authorship practices can vary across different disciplines, authorship should reflect the individuals who have made a substantial contribution to the research project, take public responsibility for the paper’s content, and agree to its submission for publication. In real life, the article is usually authored by at least one truly genuine author and some parasitic authors. The first author and the last author are especially important. The middle authors are less important, and their participation is often wrongly seen as an inconsequential decorative favor. The honorary author, a gift or guest author, is added as a bonus to please someone higher in the hierarchy than the submitting author. This practice is believed to enhance the chances of publication, but usually, the excess of honorary authors will make reviewers more critical. A ghost author contributed substantially but it does not appear in the list of authors to avoid declaring an overt conflict of interest. The gold author is someone paid by a third party in direct or indirect forms, and capable of writing and signing everything asked by the payer, including overstating the merits of a new drug or ignoring its drawbacks. A fake author does not exist, and while it may seem humorous it is a breach of scientific integrity and can lead to serious consequences for the individuals involved. With Chat-generative pre-trained transformer (Chat-GPT), artificial intelligence may contribute decisively to the article content and presentation. Overall, it is important to maintain high standards of integrity and transparency in authorship practices to ensure that research findings are trustworthy and reliable. The reputation of your work is in the hands of your coauthors, so choose them carefully and make sure they share your commitment to scientific integrity.